Analisis Dampak Perilaku Bullying terhadap Perkembangan Karakter Peserta Didik di SDN 1 ASTANA - Siti Nur Halimah; Juju Jumaroh; Mutiara Sri Dewi; Firda Amaliah; Dianasari Dianasari (Journal on Education, 2025)
This research aims to analyze bullying behavior on the character formation of students in elementary schools. In line with the research objectives, this research uses descriptive qualitative research methods. The subjects of this research were victims of bullying. The data collection method was carried out using case studies. Data collection through direct observation. The research results are as follows: (1) Analysis of bullying behavior which has been studied by researchers in the form of physical contact and verbal form so that victims of bullying experience huge obstacles in forming their character. (2) The factors causing bullying behavior are not only internal factors but there are also external factors supported by the lack of strict rules given to the school so that bullying behavior can occur repeatedly. (3) The impact of bullying behavior on students' character development is very influential, as students tend to be quiet and embarrassed to be active in learning. This teacher's role is very important to improve the character of students in elementary school.